2009
DOI: 10.1074/jbc.m109.036632
|View full text |Cite
|
Sign up to set email alerts
|

Blom7α Is a Novel Heterogeneous Nuclear Ribonucleoprotein K Homology Domain Protein Involved in Pre-mRNA Splicing That Interacts with SNEVPrp19-Pso4

Abstract: The removal of introns from pre-mRNA is performed by the spliceosome that stepwise assembles on the pre-mRNA before performing two catalytic steps. The spliceosome-associated CDC5L-SNEVPrp19-Pso4 complex is implicated in activation of the second catalytic step of pre-mRNA splicing, and one of its members, SNEVPrp19-Pso4, is also implicated in spliceosome assembly. To identify interaction partners of SNEVPrp19-Pso4, we have performed yeast two-hybrid screenings. Among the putative binding partners was a so far … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 79 publications
4
27
0
Order By: Relevance
“…As expected, full length Blom7α mainly localized to the nucleus of Hela cells, as we already described for the endogenous protein [6]. This was also true for all mutants containing the region between amino acids 480 and 549.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…As expected, full length Blom7α mainly localized to the nucleus of Hela cells, as we already described for the endogenous protein [6]. This was also true for all mutants containing the region between amino acids 480 and 549.…”
Section: Resultssupporting
confidence: 87%
“…This was also true for all mutants containing the region between amino acids 480 and 549. However, mutants lacking this part and containing the KH motifs localized to nucleus, as well as cytoplasm, as was already described for Blom7γ, which is composed of the KH domains and the γ-specific C-terminus alone [6]. The cytoplasmic staining fully co-localized with RNA counterstained by Pyronin Y (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Moreover, KIAA0907 was found as a SF1 partner with very high confidence in all cell types tested. Roles in splicing for this protein, also termed BLOM7, have been described ( 60 ). It contains a KH domain, similar to a few other proteins found in the Y2H screens with a lower PBS.…”
Section: Resultsmentioning
confidence: 99%
“…Another protein with a high PBS found in all cell types analyzed is KIAA0907/BLOM7. It was initially identified in Y2H screens with a component of the human Prp19 complex and has been shown to increase splicing in HeLa cell nuclear extracts and regulate alternative splice site decisions ( 60 ). BLOM7 contains two KH domains, the second of which is comprised in the SF1 ΣSID.…”
Section: Discussionmentioning
confidence: 99%
“…In general, trans-acting factors that regulate alternative splicing include SR (Ser-Arg) proteins and heterogeneous nuclear ribonucleoproteins (hnRNPs) particles (Chen and Manley 2009). Recent studies showed that hPrp19 interacts directly with Blom7α, a novel hnRNP K homology domain-containing protein that can modulate the alternative 5 ′ and 3 ′ splice site choices of reporter minigenes (Grillari et al 2009). In addition, CDC5L/PLRG1 interacts with hnRNP M and affects the selection of alternative splice site (Lleres et al 2010).…”
Section: Structure-function Relationship Of Bcas2mentioning
confidence: 99%